PERBANDINGAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA DENGAN FATWA NOMOR 68/DSN-MUI/III/2008 TENTANG RAHN TASJILY - Witra Yosi; Aidil Alfin; Basri Na'ali (Tamaddun, 2018)
This article discusses the substance of fiduciary guarantees according to Law Number 42 of 1999 concerning fiduciary guarantees with the substance rahn tasjily according to fatwa Number 68 / DSN-MUI / III / 2008. In addition, it is also to find out the legal comparison between fiduciary guarantees according to Law Number 42 Year 1999 and rahn tasjily according to fatwa Number 68 / DSN-MUI / III / 2008. The method used in this research is descriptive comparative analysis. Namely by comparing the substance of fiduciary guarantees according to Law Number 42 of 1999 with rahn tasjily according to DSN Fatwa Number 68 of 2008 as well as the similarities and differences between the two. The conclusion of this research is that the substance of the fiduciary guarantee according to Law No. 42 of 1999 is an agreement in which the debtor binds his agreement to the creditor for the accounts receivable debt which makes proof of ownership of an object to be used as collateral accompanied by an interest. While the substance of rahn tasjily according to fatwa Number 68 / DSN-MUI / III / 2008, namely the rahin binding agreement to the murtahin by using the qardh agreement (accounts receivable debt) accompanied by a collateral / collateral in which the collateral remains in control (utilization) rahin and proof of ownership submitted to the murtahin and ijarah rates in exchange for the cost of maintaining proof of ownership of the collateral. The legal comparison between fiduciary guarantees according to Law Number 42 of 1999 and rahn tasjily according to fatwa Number 68 / DSN-MUI / III / 2008 has similarities in the status of the collateral, the form of the agreement, subject, termination or deletion of the agreement and the method of execution of the object be a collateral object. While the difference lies in the maintenance of objects that are used as collateral for debt, in terms of binding guarantees, in terms of cancellation or transfer of rights by one party, in terms of the transfer of ownership rights and in terms of the mechanism of practice.